Steps Forwards in Diagnosing and Controlling Influenza - Mohammad Baddour, Manal (IntechOpen, 2016)
The World Health Organization (WHO) estimates that 3-5 million cases of severe influenza worldwide will result in 250,000-500,000 deaths annually. Collectively, data are shared via the WHO's Global Influenza Surveillance and Response System (GISRS), which includes 143 institutions in 113 WHO member states, to help alert the emergence of antigenic variants or the beginning of a pandemic. In April 2009, the Centers for Disease Control and Prevention (CDC) cited the first incidence of human-to-human transmission of pandemic H1N1, also referred to as swine influenza A, which was antigenically distinct from other circulating human H1N1. As the first influenza pandemic of the twenty-first century, pandemic H1N1 was not included in the annual trivalent vaccine regimen, leaving a large majority of the population unprotected from the newly emerging pathogen.